1984
DOI: 10.1159/000128432
|View full text |Cite
|
Sign up to set email alerts
|

The Role of A-O-Incompatible Blood Transfusions in Porcine Orthotopic Liver Transplantations

Abstract: The consequences of administrations of A-O-incompatible blood transfusions during porcine orthotopic liver transplantations (OLT) are described. Two series, both subjected to the same standard procedure except for the administration of compatible or incompatible blood, are compared. The striking differences in peroperative and direct post-operative morbidity, mortality, and causes of death between the two series are presented. Although not generally applied, blood transfusions in experimental surgery should un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Hunfeld et al. [61] did a careful study, where they showed that pigs that received A–O incompatible transfusions developed pulmonary hypertension and decreased fibrinogen with an associated increase in fibrin degradation products. Eight of 15 pigs died during or shortly after surgery due to hemorrhage and four pigs died due to severe bronchospasm.…”
Section: Red Blood Cell Transfusionsmentioning
confidence: 99%
“…Hunfeld et al. [61] did a careful study, where they showed that pigs that received A–O incompatible transfusions developed pulmonary hypertension and decreased fibrinogen with an associated increase in fibrin degradation products. Eight of 15 pigs died during or shortly after surgery due to hemorrhage and four pigs died due to severe bronchospasm.…”
Section: Red Blood Cell Transfusionsmentioning
confidence: 99%
“…Despite striking ameliorations in extracorporeal liver perfusion, including the use of silastic tubes, precision roller pumps, efficient blood filters, and the so-called pump circulation of the liver which allowed to simulate physiologic conditions, the function of the isolated liver is highly dependent on the blood used in the ECC. In the literature, this prime volume of 1,000-1,500ml (600ml in our study) has been obtained by various procedures [1,4,7]. Heterologous blood has shown to be inferior to homologous blood, especially in long-term perfusions [7].…”
Section: Discussionmentioning
confidence: 78%
“…In the literature, this prime volume of 1,000-1,500ml (600ml in our study) has been obtained by various procedures [1,4,7]. Heterologous blood has shown to be inferior to homologous blood, especially in long-term perfusions [7]. However, severe impairment of liver function due to genetic disparity was not observed [2].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations